Cloning in Plants and Animals: Divergent Pathways and Ethical Boundaries in Biotechnology - Akram, Muhammad; Umaru, Isaac John; Aslam, Nosheen; Hasan, Mohammed Khudhair; Abdulghafoor, Hind A.; Khan, Fahad Said; Ozdemir, Fethi Ahmet; Sołowski, Gaweł; Ali, Jaouher Ben; Al-Musawi, Jehan Mohammed; Mahmood, Abid (African Journal of Biochemistry and Molecular Biology Research, 2025)
The creation of genetically identical creatures by cloning is essential to contemporary biotechnology, agriculture, and medical research. Although the basic idea of cloning is the same in all kingdoms, there are substantial differences between plants and animals in terms of its use, effectiveness, and moral consequences. Cloning is a common, natural occurrence in plants and is frequently accomplished using asexual reproduction procedures such as tissue culture, grafting, and vegetative propagation. Because plant cells are highly totipotent, practically any somatic cell may grow again into a whole organism given the right circumstances. The production of genetically engineered plants with enhanced features, the preservation of uncommon species, and the large-scale multiplication of genetically uniform crops have all been made easier by this regenerative potential. Animal cloning, on the other hand, poses far more biological and technological difficulties. Due to developmental errors, aberrant gene expression, and insufficient reprogramming of the donor nucleus, this procedure usually has poor success rates and necessitates intricate management. It brings up important issues about biodiversity, animal care, and the ethical ramifications of cloning sentient creatures. Furthermore, animal cloning is more closely regulated and scrutinized by the public than plant cloning, which is generally recognized in agricultural operations and conservation initiatives. This is particularly true when it comes to food production and possible human cloning. The difference in the effectiveness and uses of cloning is mostly explained by the difference in totipotency between plant and animal cells. The accuracy of modification is becoming closer thanks to recent technological advancements like CRISPR-Cas9, yet the ethical and practical possibilities of cloning in these two domains are still not comparable. The intricate relationship between biological viability, technical development, and societal acceptability of interspecies cloning is shown by this comparative study. Guidance on the proper application and control of cloning technologies in biomedicine and agriculture depends on an understanding of these distinctions.